ASSESSMENT OF ICT AND SOCIAL MEDIA UTILIZATION AMONG FISH SELLERS IN SABON GARI MARKET FOR ENHANCING DIGITAL INNOVATION IN FISH MARKETING - Attahir, M.; Ibrahim, H.; Muazu, K.; Said, A.S.; Iliyasu, F.B.; Rano. B.Y. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the utilization of Information and Communication Technology (ICT) tools and social media platforms among fish sellers in Sabon Gari Market, Kano State, Nigeria, with the aim of enhancing digital innovation in fish marketing. A multi-stage sampling technique was employed to select 130 respondents. Data were collected using a well-structured questionnaire and analyzed using descriptive and inferential statistics. The results revealed that 70% of respondents were aged between 41–50 years, 73.3% were male, and 87.7% were married. Majority (70.2%) had completed secondary education, while 86.9% were members of cooperative societies. Most 81.1% of the respondents earned between ₦50,000 to ₦100,000 monthly. ICT adoption was moderate (66.9%), with digital scales (36.2%), POS machines (33.1%), and smartphones (29.9%) being the most commonly used tools. WhatsApp was the most widely used social media platform for communication with customers (69.3%), while its usage for online sales and marketing was limited. Logistic regression results showed that WhatsApp usage significantly enhanced business performance (Exp(B) = 5.276, p < 0.01), whereas TikTok and Twitter/X negatively influenced utilization. Major barriers to adoption included inadequate awareness (36.2%), limited digital skills (33.1%), and high device costs (18.9%). The study concludes that although ICT and social media have potential to enhance fish marketing efficiency, adoption remains constrained by digital illiteracy and infrastructural challenges. It recommends targeted digital literacy training, subsidized ICT devices, and gender-inclusive interventions to promote equitable participation and digital innovation among fish sellers.